ASSESSMENTS FREQUENCY OF ORAL FUNGAL INFECTION WITH TYPE 2 DIABETES MELLITUS IN IRAQI PATIENTS (Academicia Globe: Inderscience Research, 2022)
Type 2 diabetes mellitus (T2DM) is a complex metabolic disorder with a vital genetic component. Recently, there was a positive association between the prevalence of oral fungal infection and disease. The current study aimed to assess the frequency and prevalence of oral fungal infection in T2DM in Iraqi patients. Methods: seventy-five patient swabs were collected from oral and same numbers from the healthy person as control with age range (40-46 years ) and different genders. The routine methods and advanced techniques such as the Vitek 2 system were used to identify organism species. Result: Our findings indicated that C.albicans were more frequently associated with T2DM patients than healthy controls, with 32 (42.7%) of T2DM patients infected vs 12(16%) healthy controls. There is a clear role of glucose concentration in serum patients with the distribution of fungi and their impact on them. Candida albicans recovered from 32 out of 46 patients, with mean glucose concentration (192.7 ±28.6), followed by C.krusei and C.ciferrii, isolated from five patients with mean glucose concentrations of (216.3± 7.1 and 221), respectively. Conclusion: Candida albicans, C.krusei and C.ciferrii were high frequency with T2DM and increased in patients with a high mean concentration of glucose.